2016
DOI: 10.1002/psc.2872
|View full text |Cite
|
Sign up to set email alerts
|

An efficient solid‐phase synthesis of peptidyl‐N‐acetylguanidines for use in native chemical ligation

Abstract: In the modern protocols of chemical protein syntheses, peptide-α-thioesters have been used as key components for the assembly of full-length polypeptides through chemoselective peptide coupling reactions. A variety of thioester precursors have been developed for the synthesis of the peptide-α-thioesters by Fmoc solid phase peptide synthesis (Fmoc-SPPS). Recently our group found a peptidyl-N-acetylguanidine as a new peptide-α-thioester precursor. This peptide derivative can be converted into a corresponding pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…In terms of the preparation of peptide thioacids, the current experiments described here used SPPS. Because several groups have reported the preparation of peptide thioacids from peptide thioester and peptide hydrazide, we can use longer peptide thioacids that can be prepared from peptide thioesters by an Intein system , or chemical thioesterification method with E. coli expression methods. However, dependent on peptide sequence and length, the combination of DDC with NCL and EPL is more practical for the preparation of the N-terminal long peptide of glycoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the preparation of peptide thioacids, the current experiments described here used SPPS. Because several groups have reported the preparation of peptide thioacids from peptide thioester and peptide hydrazide, we can use longer peptide thioacids that can be prepared from peptide thioesters by an Intein system , or chemical thioesterification method with E. coli expression methods. However, dependent on peptide sequence and length, the combination of DDC with NCL and EPL is more practical for the preparation of the N-terminal long peptide of glycoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…Okamoto et al synthesized peptide‐ N ‐acetaminoguanidine Fmoc‐SPPS by solid‐phase method. This method has no obvious reaction to acetaminoguanidine, and the synthesis efficiency of peptide‐ N ‐acetaminoguanidine is high 91 …”
Section: Production Methods Of Bioactive Peptidesmentioning
confidence: 99%
“…This method has no obvious reaction to acetaminoguanidine, and the synthesis efficiency of peptide-N-acetaminoguanidine is high. 91 Yu et al demonstrated a hybrid solid solution-phase connection method that combines the efficiency of solidphase connection and solution-phase connection in the total synthesis of modified histone proteins. The study maximized product yield by performing resin cleavage at the external Rink linker, followed by cleavage at the internal cyclohexamethylenebisacetamide linker to generate natural carboxyl ends.…”
Section: Solid-phase Peptide Synthesismentioning
confidence: 99%